FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Natasha Natasha; Lukman Surjadi (Jurnal Paradigma Akuntansi, 2023)
This study aims to analyze and obtain empirical evidence about the effect of liquidity, leverage, sales growth, and firm size on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample selection technique used in this study was purposive sampling with a total sample of 80 manufacturing companies. The data processing technique uses multiple linear regression method with Eviews 12 software. The results of this study indicate that liquidity and leverage do not have a significant effect on financial performance, sales growth has a significant positive effect on financial performance, and firm size has a significant negative effect on financial performance.